CREATION OF MULTIMEDIA ELECTRONIC EDUCATIONAL METHODOLOGICAL COMPLEXES FOR THE COURSE OF INFORMATICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article gives a definition of the educational-methodical complex (TMC) as one of the types of electronic textbook of modern computer teaching aids, considers the main functions that must be solved by the TMC in the discipline Informatics for students of the direction of Preschool education, and also suggests the main stages of its application.